Applications of the Concept of Territorial Marketing in Forming and Implementing Competitive Advantages for Tourist Areas - KUTTUBAEVA, Toskanay Аitmukanovna; ISHCHUK, Lyudmila Viktorovna; ADARINA, Raisa Taanovna; GLOTKO, Andrei Vladimirovich; FEDOSOVA, Tatyana Viktorovna (Journal of Environmental Management and Tourism, 2017)
This paper analyzes the use of territorial marketing in forming and implementing competitive advantages of tourist areas in the Republic of Altai. It provides the definition of a tourist area as well as its general and specific features. It also considers the directions of implementing competitive advantages of a tourist area. The influence of the natural potential of the Altai Republic on the development of different kinds of tourism is shown. The structure of a territorial tourist product of the Altai Republic is offered; the emphasis is placed on the development of active kinds of tourism (sports and hunting, mountain-skiing, recreation). The mechanism of brand formation and building of an area and a territorial tourist brand in six directions is specified.